2019
DOI: 10.1016/j.isci.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Ag2S Micro-rods-Enhanced Fluorescence on Liquid Crystals: Cation-π Interaction-Triggered Aggregation-Induced Emission Effect

Abstract: Summary Aggregation-induced emission (AIE) system has long been regarded as a promising substitute to overcome the aggregation-caused quenching in traditional luminescent liquid crystals, which could further enhance its efficiency and application. However, due to the intrinsic weak interaction between hybrid components, heterogeneous inorganic materials-induced AIE process was rarely reported. In this study, trace amounts of amorphous Ag 2 S microrods and an AIE-active liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…As shown in Figure 2 c, the volume of generated foam reaches up to 350 mL after ventilating for 5 min, and the foam volume is not affected by the ventilation time. However, because of the vigorous movement of the liquid molecules at high temperature, 23 , 24 the foam volume decreases from 350 to 265 mL as the temperature rises to 88 °C, which can also be confirmed by the defoaming time at different temperatures. As the temperature increases from 25 to 35 °C, the deforming time increases slightly.…”
Section: Resultsmentioning
confidence: 76%
“…As shown in Figure 2 c, the volume of generated foam reaches up to 350 mL after ventilating for 5 min, and the foam volume is not affected by the ventilation time. However, because of the vigorous movement of the liquid molecules at high temperature, 23 , 24 the foam volume decreases from 350 to 265 mL as the temperature rises to 88 °C, which can also be confirmed by the defoaming time at different temperatures. As the temperature increases from 25 to 35 °C, the deforming time increases slightly.…”
Section: Resultsmentioning
confidence: 76%
“…Specifically, through a simple wet chemical method, sliver nitrate (AgNO 3 ) and dimethyl sulfoxide (DMSO) were reacted to prepare Ag-DMSO complex nanorod precursors with a diameter of approximately 300 nm and a length of approximately 2 μm. 18 The inherent coordination direction of DMSO is the primary driving force for the formation of the 1D morphology. Upon irradiation of the complex precursor, DMSO decomposes and volatilizes from the precursor, and the atomic arrangement of Ag 2 S is destroyed, resulting in amorphous Ag 2 S nanorods (Figure 2a).…”
Section: One-dimensional Amorphous Nanomaterialsmentioning
confidence: 99%
“…the reasonable enhancement mechanisms are highlighted. 18,[41][42][43]55,56 We used amorphous ZnO nanocages as a SERS substrate and observed a SERS enhancement factor (EF) as high as 6.62 × 10. 5,42 X-ray absorption near-edge structure (XANES) characterization and first-principles density functional theory (DFT) calculations showed that the amorphous structure with a low coordination number and the abundant oxygen defects in the ZnO nanocages had a higher electronic density of states and a narrower energy gap, resulting in a higher SERS activity than the corresponding crystalline compound.…”
Section: Electrocatalytic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…然而, 由于杂化组分间固有的弱相互作用, 非均质无机材料诱导的 AIE 过程鲜有报道. 最近, 唐本 忠等[163] 用非晶态 Ag 2 S 棒作为聚集中心, 探究无机纳米 颗粒对 AIE 液晶发光性能的影响. 向液晶中引入微量非 晶态 Ag 2 S 和化合物 75, 所得复合材料的荧光强度增强 了 36 倍.…”
unclassified